Lives in architecture : Terry Farrell. - Farrell, Terry (RIBA Publishing, 2020)
Terry Farrell is one of Britain's most influential architects of the twenty-first century. Offering a compelling personal account of his life in architecture as an influential postmodern designer, architect-planner and principal of a leading global practice, this autobiography includes anecdotes and invaluable insights into Terry's life and work from the 1940s to the present day. An inside view of what it's like to be an architect at the top of his profession, this book also highlights what it takes to develop a successful international practice. Offers the inside view of what it is like to be an architect at the top of his profession, including insights into the defining projects and watershed moments of Sir Terry Farrell's career Provides the inside story on some of Terry Farrell's most significant buildings and projects, including Charing Cross Station, The MI6 Building, Alban Gate and Beijing South Railway Station Abundantly illustrated with over 80 images, including personal photos and images of key buildings.